Optimization Guidance and Counseling of Satbinmas to Fraud Prevention in The Jurisdices of Polrestabes Bandung - Tinumbang, Ryasa (Advances in Police Science Research Journal, 2020)
This research’s background is the rise of fraud crimes in Bandung City – it became one of the highest recorded crimes in Bandung within the last three years. Conducting preventive efforts would be the most effective counter-act to that. However, preventive efforts by the Satuan Binmas of Polrestabes Bandung (henceforth Satbinmas) haven’t been optimal. Hence, this research focused on understanding how the Satbinmas conducts guidance and counseling activities in preventing fraud crimes, and what factors influence those activities. The qualitative research method was used, while data was collected through interviews, observations, and document analysis. This research found that the Satbinmas haven’t conducted guidance and counseling activities completely in accordance with Articles 8, 9, 10, and 11 of Perkap 21/2007. This is indicated by findings of unfulfilled indicators in the planning, implementation, and evaluation of the activities. The research also found 9 factors that influence the Satbinmas’ implementation of guidance and counseling activities. Those include human resources, organizational policy, organization structure, facilities and infrastructure, budget, activity materials, other supporting functions, and how the criminal code defines fraud, all of which are then analyzed using the 6M Theory of Management. Based on the findings, the author recommends that the Kasat Binmas of Polrestabes Bandung: formulate a specific program to handle fraud cases, optimize the implementation of guidance and counseling activities according to Perkap 21/2007, and directly supervise the implementation of those activities. Meanwhile, closer attention is needed for several influencing factors, including human resources training, incidental needs budget, and facilities and infrastructure fulfillment.